PENGEMBANGAN MEDIA PEMBELAJARAN DIORAMA BERBANTU KARTU QR CODE UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS 4 SD NEGERI CAKUNG TIMUR 05 PAGI - Rahma Indah Mawarni; Awalina Barokah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Low student motivation in learning photosynthesis material is influenced by the lack of innovation in instructional media. Therefore, it is necessary to develop a dioramabased learning media supported by QR code cards that present learning materials through engaging illustrations during the learning process. This study aims to develop QR code-assisted diorama media and to enhance students’ learning motivation. The research employed a Research and Development (R&D) method using the ADDIE model. The results showed that the QR code-assisted diorama media was deemed "highly feasible," with an average validation score of 99% from three expert validators. Furthermore, the media was considered "highly effective," with the student motivation questionnaire scoring 87%. It can be concluded that the QR code-assisted diorama media is effective as an IPAS learning tool to improve the learning motivation of fourth-grade students at SD Negeri Cakung Timur 05 Pagi.